BURDEN OF PROOF IN CRIMINAL AND CIVIL PROCEDURE - Brkić, Snežana S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In this paper the author presents the evolution of burden of proof in criminal and civil procedure. In civil procedural law there are the differences between the burden of proof in subjective, and that in objective sense.  In criminal procedural law there are the differences between the burden of proof in formal, and that in material sense.The burden of proof in objective sense and the burden of proof in material sense is a specific working method available to court after the evidence procedure is carried out,  when the use of free assesment of evidence method did not result in its conviction that a certain disputed legally relevant fact is true, which disables the court to form the factual substratum of the judgment. A particular attention is paid to the discussion of the principle in dubio pro reo and its differences from burden of proof in civil procedure.
Keywords: in dubio pro reo; civil procedure; criminal procedure; material burden of proof; formal burden in proof; objective burden of proof; subjective burden of proof